Relationships Between Aphids (Insecta: Homoptera: Aphididae) and Slugs (Gastropoda: Stylommatophora: Agriolimacidae) Pests of Legumes (Fabaceae: Lupinus). Issue 1 (20th June 2016) - Kozłowski, Jan; Strażyński, Przemysław; Jaskulska, Monika; Kozłowska, Maria
Abstract: Lupin plants are frequently damaged by various herbivorous invertebrates. Significant among these are slugs and aphids, which sometimes attack the same plants. Relationships between aphids, slugs and food plant are very interesting. Grazing by these pests on young plants can lead to significant yield losses. There is evidence that the alkaloids present in some lupin plants may reduce grazing by slugs, aphids and other invertebrates. In laboratory study was analyzed the relationships between aphid Aphis craccivora and slug Deroceras reticulatum pests of legumes Lupinus angustifolius. It was found that the presence of aphids significantly reduced slug grazing on the plants. The lupin cultivars with high alkaloid content were found to be less heavily damaged by D. reticulatum, and the development of A. craccivora was found to be inhibited on such plants.